THE IMPROVEMENT OF GENERATION Z FINANCIAL WELL-BEING IN PEKANBARU - Nicholas Renaldo; Sudarno Sudarno; Hutahuruk Br. Marice (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2020)
The current economic condition of generation Z was pretty unexpected. It might trigger problems personally or even their families. This study aimed to reveal the factors influencing the financial well-being and altering personality problems of generation Z. There were more than 800,000 peoples in population and the number of the sample was 239 peoples using a combination of purposive and convenience sampling methods. The data was then analyzed using multiple linear regression. The researchers used primary data by distributing questionnaires based on a Likert Scale. All classic assumptions met the criteria and testing produced financial self-efficacy, financial attitude, financial knowledge, financial behavior, and had a significant positive effect on financial well-being. However, locus of control had no significant effect on financial well-being. Generation Z must increase their independence and confidence to achieve what they want. It would be good to have financial atitude and investment behavior along with financial knowledge. They must also believe that only theirself can provide personal well-being. Generation Z needed character education, more mature, and independent thinking models to deal with economic problems